Eksistensi Hukuman Mati di Indonesia - A. Hasyim Nawawie (Institut Agama Islam Tribakti (IAIT) Kediri, 2017)
This study aims the death penalty in Indonesia. We know where the death penalty is contrary or not in terms of the constitution and Islamic law, then we can conclude that if the legal implementation of the death penalty in Indonesia continue to be done or should be abolished. Based on research and the analysis conducted, conclude that Indonesia According to the Indonesian Constitution that the death penalty in Indonesia is constitutional. Constitutional Court Decision No. 2-3 / PUU-V / 2007 states that the imposition of the death penalty was constitutional. Any law governing capital punishment is not contrary to the Constitution of the State of Indonesia. However the legislation in Indonesia death penalty is still recognized in some legislation. There are three groups of rules, namely: Criminal Dead in the Criminal Code, Criminal die outside the Criminal Code, Criminal die in the Draft Bill. According to Islamic law that the death penalty could be applied to some criminal act or jinazah, either hudud qishahs, diyat or ta'zir among others to: Apostate, Rebel, Zina, Qadzaf (Allegations Zina), Steal (Corruption), Rob (Corruption), Murder.